Synthesis and Surfactant Properties of Alpha-Sulfonated Polyhydric Alcohol Ester (ASPA) - Ahmed Nur, Adam Ibrahim (1999)

(untitled)
A new anionic surfactant, alpha-sulfonated polyhydric alcohol ester (ASPA) was prepared by transesterification of palm-based alphasulfonated methyl ester (SME) or by esterification of palm-based aJphasulfonated fatty acid (SFA) with glycerol in non-solvent media. The product was isolated as sodium salt by crystallization using methanol as solvent. The purity of the product was confirmed by TLC, yielding a single spot while the melting point was found to be sharp at 3SoC. The structure of the ASPA was identified by Fourier Transform Infrared (FTIR) and confirmed by 1 H and 13C n uclear magnetic resonance spectroscopy (NMR). FTIR analysis of ASPA from SME indicated the presence of broad OH group at wavenumber 3402 cm-1, while the presence of OH group in ASPA from SFA was detected at 3397 cm-1. The presences of CH20H and CHOH groups of ASPA molecule via SME were indicated by peak 8 at 3.6 and 3.7 ppm respectively in 1 H-NMR spectrum. The two OH groups also appeared at 4.25 and 4.27 ppm corresponding to primary and secondary alcohols respectively. The 1 H-NMR of ASPA via SFA showed the overlapping of CH20H/CHOH at 3.6 ppm and the two OH groups also overlapped at 4.11 ppm. The 13C-NMR of ASPA via SME showed the presence of carbon primary alcohol at 70 ppm and carbon secondary alcohol at 72 ppm, while the carbon primary alcohol and carbon secondary of ASPA via SFA were overlapped at 72 ppm. The effects of reaction temperatures, reaction times and catalyst on the synthesis were also evaluated. The maximum yield of ASPA via SME was 48%, at the reaction temperature of 70°C and the reaction time of 50 minutes, while the optimum yield of ASPA via SFA was 95%, at reaction temperature of 40°C and the reaction time of 60 minutes. These new products gave low surface tension (26 dyne/cm). Other properties, such as foaming power/stability, wetting ability and anti-rust power were evaluated. The washing active substance (YVAS) as a function of aging time was also studied.